Review of the paper wasps of the Parapolybia indica species-group (Hymenoptera: Vespidae, Polistinae) in eastern parts of Asia - Saito-Morooka, Fuki; Nguyen, Lien T. P.; Kojima, Jun-Ichi (Zootaxa, 2015)
Nine species of the Parapolybia indica species-group in eastern parts of Asia are reviewed. Four new species are described: P. flava sp. nov. (Vietnam), P. crocea sp. nov. (Japan), P. nana sp. nov. (Vietnam), and P. albida sp. nov. (Vietnam). Parapolybia indica (de Saussure, 1854), P. bioculata van der Vecht, 1966 and P. tinctipennis (Cameron, 1900) are redescribed. The status is reinstanted for P. fulvinerva (Cameron, 1900), stat. resurr. and P. tinctipennis (Cameron, 1900), stat. resurr. and new status is proposed for P. bioculata van der Vecht, 1966, stat. nov. Parapolybia tinctipennis (Cameron, 1900) is newly recorded from China, Vietnam and Laos. The key to species is given. The nests of P. indica, P. bioculata, P. tinctipennis, P. flava and P. crocea are remarked.